Nanotechnology in Kidney and Islet Transplantation: An Ongoing, Promising Field - Wang, Wei; Teng, Ya; Xue, Ji-Ji; Cai, Hong-Kai; Pan, Yu-Biao; Ye, Xing-Nan; Mao, Xin-Li; Li, Shao-Wei (Frontiers in Immunology, 2022)
Organ transplantation has evolved rapidly in recent years as a reliable option for patients with end-stage organ failure. However, organ shortage, surgical risks, acute and chronic rejection reactions and long-term immunosuppressive drug applications and their inevitable side effects remain extremely challenging problems. The application of nanotechnology in medicine has proven highly successful and has unique advantages for diagnosing and treating diseases compared to conventional methods. The combination of nanotechnology and transplantation brings a new direction of thinking to transplantation medicine. In this article, we provide an overview of the application and progress of nanotechnology in kidney and islet transplantation, including nanotechnology for renal pre-transplantation preservation, artificial biological islets, organ imaging and drug delivery.